EFFECT OF ACTIVE FRACTIONS OF Gracilaria edulis EXTRACT IN INDUCING APOPTOSIS OF MCF-7 - Rahadiani, Pratiwi
Seaweed is one of potential Indonesian natural resources. Its habitat spread throughout Indonesia Ocean and reach 1.2 million ha. In 2014, total product of seaweed reaches about 237.8 thousand tons production (56% of world total production). Bioactive compounds of seaweed have broad biological activities especially as an anticancer. In the last few decades, anticancer activity of seaweed extract and bioactive compounds has gained interest from researchers around the world. It happens because of the need for anticancer alternative candidate with more efficacious, specific, and has few side effects than currently available chemotherapy drugs. In addition, diets containing seaweed have been known to reduce cancer risk. The success of an anticancer drug candidate in inducing apoptosis is one of the determining of success in developing cancer therapy.